Pemahaman Praktisi BMT di Yogyakarta Terhadap PSAK No. 59 (Akuntansi Perbankan Syariah) Pengakuan dan Pengukuran Produk Funding - Eny lroh Hayati (Millah: Journal of Religious Studies, 2008)
The objective of this research is to explore BMT practitioners' understanding about the SFAS No. 59 on Shari'ate Banking Accountancy for finding product. For this reason, the research is conducted using descriptive method. Field research using quantitative approach is also used. However, qualitative approach is also used to explore and to clarify as well as to compare between the concept and the real situation. The population used in this study is member of PUSKOP¬SYAH DIY, and the subjects of this research are the managers and accounting staff of these BMTs. The sample consists of 30% of 80 active members. However, since the magnitude of each sub-population is different, proportional sampling method is used to determine the number of sample taken from each sub-population, and purposive sampling method is used as the sampling method. The independent variables used in this research are age, educational background, the length of time working in BMT, and the frequency of training or workshop joined by the subjects. Meanwhile, the dependent variable in this research is the BMT practitioners' understanding about SFAS No. 59 for funding product. Data gathering method used in this research was questionnaire, field observation and interview. Meanwhile, data analysis for this study includes descriptive statistical analysis and inferential statistical analysis.Keywords: akuntansi, PSAK No. 59, pemahaman, Praktisi BMT